Узагальнена модель оцінки показників функціонування низькошвидкісних мереж зв`язку автоматизованих систем управління - Стрелковська, Ірина Вікторівна; Стрелковська, І. В.; Стрелковская, Ирина Викторовна; Strelkovska, Iryna V.; Золотухін, Р. В.; Григор’єва, Тетяна Ігорівна; Григор’єва, Т. І. (My University, 2022)
При проектуванні системи зв’язку для автоматизованих систем управління державного рівня в низькошвидкісних мережах зв’язку на базі ультракороткохвильових радіостанцій основною проблемою є обґрунтований вибір необхідного телекомунікаційного обладнання для побудови мереж зв’язку з необхідними функціональними характеристиками для забезпечення доступності сервісів. В роботі проводиться аналіз концепції використання протоколів JDSS та NFFI, трьохрівневої ієрархічної моделі компанії Cisco та узагальненої організаційної структури системи зв’язку підрозділу низової ланки управління. На основі проведеного аналізу запропоновано узагальнену архітектуру АСУ низової ланки управління в низькошвидкісних мережах зв’язку на базі УКХ радіостанцій, що складається з трьох основних рівнів: рівня доступу, рівня взаємодії та рівня керування. Показники трафіку в низькошвидкісних мережах зв’язку на базі УКХ радіостанцій та підвищенні вимоги до передачі інформації в АСУ тактичної ланки управління призводить до неможливості використання існуючих моделей щодо оцінки показників функціонування в низькошвидкісних мережах зв’язку АСУ. В роботі запропоновано узагальнену модель показників функціонування мережі зв’язку АСУ, обчислено ймовірності обслуговування та ймовірність відмови в обслуговуванні кожного рівня узагальненої архітектури АСУ.

The main problem, when designing a telecommunication system for governmental automated control systems is the reasonable choice of the necessary communications equipment to build networks with the required functional characteristics to ensure the availability of services. The paper considers the governmental automated control systems of the lower level of management with the active movement of users in low-bandwidth communication networks based on UHF/VHF radio stations with high requirements for efficiency, security, reliability, survivability and scalability. Such systems are widely used in the management of enterprises, production, military, public organizations and public administration. The paper analyzes the concept of using the JDSS and NFFI protocols, the three-level hierarchical model of Cisco and the generalized organizational structure of the communication system of the lower level management unit. Proposed a generalized architecture of automated control system of the lower management level in low-bandwidth communication networks based on UHF/VHF radio stations, which consists of three main levels: access level, interaction level and control level. Atypical indicators of traffic in low-bandwidth communication networks based on UHF/VHF radio stations and increasing requirements for the transfer of information to the tactical management automated control system makes impossible to use existing models to assess performance in low-bandwidth automated control system networks. The paper proposes a generalized model of indicators of the automated control systems communication network and calculating the probability of service and the probability of failure each level of the generalized architecture. The obtained results allow determining the availability of services in low-bandwidth communication networks of automated control systems of the lower management level with active movement of users based on UHF/VHF radio stations, which will increase the efficiency of load calculations on communication channels and reduce the probability of service failures.
Стрелковська І. В. Узагальнена модель оцінки показників функціонування низькошвидкісних мереж зв`язку автоматизованих систем управління / І. В. Стрелковська, Р. В. Золотухін, Т. І. Григор’єва // Інфокомунікаційні та комп’ютерні технології, № 1 (03), 2022. - С. 153-169. https://doi.org/10.36994/2788-5518-2022-01-03-09
Keywords: автоматизовані системи управління; низькошвидкісні мережі зв’язку; архітектура мережі; трьохрівнева ієрархічна модель; JDSS; NFFI; AdataP-36; узагальнена архітектура; модель; ймовірність обслуговування; ймовірність відмови в обслуговуванні; automated control systems; low-bandwidth communication networks; network architecture; three-level hierarchical model; JDSS; NFFI; AdataP-36; generalized architecture; model; probability of service; probability of failure; Research Subject Categories::TECHNOLOGY